Teste de deterioração controlada e uso do sistema automatizado de análise de imagens de plântulas (SVIS®) na avaliação do potencial fisiológico de sementes de crambe - Leão-Araújo, Erica Fernandes; dos Santos, Juliana Faria [UNESP]; da Silva, Clíssia Barboza; Filho, Júlio Marcos; Vieira, Roberval Daiton [UNESP] (FapUNIFESP (SciELO), 2017)
Vigor tests are important tools for verifying the physiological potential of seed lots; however, various aspects can interfere in the consistency of the test results. The search for less subjective procedures has drawn the interest of researchers. The aim of this study was to adapt the methodology of the controlled deterioration test and verify the efficiency of the Seed Vigor Imaging System (SVIS®) to evaluate the vigor of crambe seeds. Initially, seed moisture content was determined and germination and vigor were evaluated in five seed lots. For the controlled deterioration test, the seed moisture content was adjusted to 18%, 20%, and 22%, and the results were interpreted at four and five days after sowing. The controlled deterioration test should be performed with initial adjustment of seed moisture content to 18%, and the germination test should be evaluated on the fifth day after sowing. SVIS® provided information on the vigor index and the length and uniformity of seedling development. Computerized image analysis is effective in evaluating the vigor of crambe seeds, and the uniformity of seedling development parameter offers the most consistent data.
Controlled deterioration test and use of the Seed Vigor Imaging System (SVIS®) to evaluate the physiological potential of crambe seeds
Keywords: Crambe abyssinica; Seed vigor; Software